Repertoire and Boarding Culture in Arabic Language and Literature at Ma'had Al-Jāmi'ah - Nasir, Amin; Ridwan, Murtadho (IMLA (Arabic Teacher and Lecturer Association of Indonesia), 2025)
The repertoire and culture of the dormitory play an important role in shaping language competence and appreciation of Arabic literature in the Ma'had Al-Jami'ah PTKIN environment. This study examines the dynamics of the use of Arabic in daily interactions, academic traditions, and literary activities that develop in the dormitory environment. This study uses a qualitative approach with an ethnographic study method. This study analyzes communication patterns, linguistic adaptation, and internalization of Arabic literary values ​​among students. The results of this study indicate that dormitory culture not only accelerates language acquisition, but also shapes mindsets and aesthetic expressions in literature. The results of this study also confirm that a dormitory-based linguistic ecosystem can create an effective learning environment to improve language proficiency and literary understanding. This study contributes to sociolinguistic research and Arabic language pedagogy, with implications for the development of dormitory-based curriculum for teaching Arabic language and literature at PTKIN.